Public life in flux: A journey from the 1940s to the present - Eren, Ibrahim; Aktan, Esin Ozlem Aktuglu (TAYLOR & FRANCIS AS, 2023)
This study investigates the evolution of public space and its impact on everyday life using a community-based and interpretive approach, as well as qualitative and quantitative methods and socio-spatial comparative analysis. The study focuses on three urban spaces from New York, Moscow, and Berlin, representing the sociopolitical dynamics of capitalism and socialism during the Cold War. The findings highlight the dynamic and ever-changing nature of public spaces, which constantly reproduce themselves even in unexpected circumstances. The study identifies effective socio-spatial breaking points that shape public life and emphasizes public spaces' novelty, dynamism, and political nature. Furthermore, the study reveals the intricate interplay between global events and their human-scale impact on urban spaces. This study is significant because it takes an interdisciplinary approach that combines sociology and spatial science, employing socio-spatial methods to assess the impact of public life. The study acknowledges its limitations, such as the possibility of unanticipated future effects and the need for additional research that includes a broader range of public spaces. Overall, this article contributes to the growing body of research on the relationship between global events and the novelty of urban life by providing an insightful perspective on the transformation of public life.
Keywords: public space; everyday life; global events; socio-spatial transformation; capitalism-socialism; human-scale impact; New York-Moscow; and Berlin; Social Sciences - Other Topics